Simulação dinâmica da soja, milho e feijão, cultivado sob diferentes regimes hídricos - Vivan, Gisele Aparecida (2014)
Agribusiness has high importance in the state of Rio Grande do Sul, with the incorporation of fundamental importance to maintain its competitiveness and attractiveness factor technologies. Irrigation has become among the leading technologies available, featuring as main advantages to increase productivity and reduce risks associated with droughts. The determination of productive crop responses via simulation models has elevated in recent years, combining the agricultural sector the possibility of predictions about various scenarios, among these, water availability, reducing time and costs. In the same way, performing historical analyzes of production and profitability are essential for decision making related to incorporeal technologies in agricultural practice. This study aims to determine, via simulation models, productive responses of soybean, maize and beans, grown under different water regimes by performing temporal and risk analysis of the results obtained for the region of Santiago, RS. The study was conducted in the municipality of Santiago (29° 09 'S and 54 ° 51 ' O), with crops of soybeans, corn and beans, calibration and validation of models for these cultures in the DSSat system being performed, and subsequent evaluation and compared to the available models for soybean and beans in RSAP system. In the models considered fit after evaluation, sequences of climatic data (1961-2010) and certain productive responses related to growing conditions in rainfed and under great water conditions being held temporal and annual profitability analysis were included. The Cropgro - Soybean, Ceres-Maize - and Cropgro Drybean, framed models obtained performance as very good, very good and good for simulation of the production of grain (PG) of soybean, corn and beans, respectively, and great for simulation maximum production of dry matter (MSM) for all cultures. In comparison to the productive field responses versus models available in the DSSat system and RSAP, it was observed that for soybean and bean, the simulations obtained with the DSSat minor variations for soybeans, and RSAP for beans, however, both systems showed variations considered satisfactory. For historical simulations, the upland, the three studied crops (soybean, maize and beans), showed significant reductions in production and consequent income due to the drought. In both conditions of crops (dryland and irrigated) the higher costs, income and income were associated with maize, followed by soy beans. Comparing irrigated with dryland, the bean crop showed the greatest increases in profit complementation function of water, followed by corn and soybeans. Conclude that the simulation models were presented as useful tools for determining the yield response of crops under study, and compared with rainfed crops irrigated, the last were more interesting technically and economically.